The Effect of Cryopreservation on Cytochrome Oxidase1 (CO1) Gene and the Relationship with Spermatozoa Motility of Albino Pangasius catfish (Pangasionodon hypophthalmus) - Uswatun Hasanah; Abinawanto; Alimuddin; Arief Boediono; Eni Kusrini (HAYATI Journal of Biosciences, 2023)
Cryopreservation is a technique for storing cells and tissues at very low temperatures for the possible usage of the stored cells and tissues throughout the year. Sperm cell cryopreservation in some species causes a decrease in sperm quality and DNA damage. Inappropriate cryopreservation protocols can cause changes in sperm physiology. Mitochondria are organelles that play a role in producing energy for sperm motility. Mitochondria have DNA molecules with small sizes compared to structures from nuclear DNA. This study analyzed the effect of cryopreservation on sperm motility and the Cytochrome Oxidase1 (COI) gene. The CO1 gene in mitochondrial DNA plays a role in energy production for spermatozoa motility. The cryopreservation was performed using skim milk and 10% methanol cryoprotectant, and the temperature in the equilibration process was 4-5°C for 10 minutes. Cryopreservation took place for 14 days in the freezer at -80°C. In addition, the thawing process was performed for 1-2 minutes at 40°C. This study found that the number of lesions per 10 kb in the CO1 gene in post-equilibration spermatozoa was (9.24±3.74), and post-thawing spermatozoa (was 10.26±7.54). Spermatozoa motility was obtained in fresh spermatozoa, i.e., 87±1.5%, post-equilibration spermatozoa 79±4.5%, and post-thawing spermatozoa 30±3.2%. This study concluded that cryopreservation of spermatozoa causes CO1 gene lesions and that in cryopreserved spermatozoa, there is a decrease in spermatozoa motility compared to fresh spermatozoa.